PENGARUH PROFITABILITAS, DEBT COVENANT DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2021 - Intan Rahma Sari; Cipto Aji Kurniato (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This research is purposed to analyze and get the evidence empirically about the influence of profitability, Debt covenant and, transfer pricing to the tax avoidance. This research is used quantitative method to collect the data. The data from this research is secondary data that obtained through the annual report and finance reports through the company official websites. The population that used in this research is the thirteen companies that registered in the stock exchange from 2016 to 2021. The writer uses purposive sampling technique as a guideline to determine the sample. This research is also used descriptive statistical analysis, data panel regression analysis, classic assumption analysis, determination of coefficient analysis and, hiphotesis analysis that used Eviews program the twelfth version.